Falconiformes assemblages in a fragmented landscape of the Atlantic Forest in Southern Brazil - Loures-Ribeiro,Alan (2006)
An ecological analysis focused on distribution of Falconiformes, comprising abundance and morphology data, is provided. Samples were collected in a fragmented landscape within the Atlantic Rainforest, southern Brazil, between August and November 2001. Four main types of habitats were pinpointed among the 30 different sampling sites, while eight external morphological traits were employed. Twenty-one Falconiformes species were detected and jackknife estimates for regional richness reached 24.8 ± 2.56 species (p<0.05). There were no differences between average number of diurnal birds of prey species in the different habitats under analysis (H-test, p>0.05). Mantel's test for relative abundance and species morphology reveals weak association rates, corroborating the lack of association between matrixes (r = 0.059, p>0.05). Difficulties in the analyses of distribution and species morphology data may have been caused by their generalist character and may be due to the high rate of environment degradation revealed by the regional landscape's mosaic aspect.